Vulnerability of adolescent students in relation to human immunodeficiency virus infection - Moreira, Anderson da Silva; Melo, Géssyca Cavalcante de Melo; Amorim, Bárbara Maria Ferreira Canuto; França, Alba Maria Bomfim de; Duprat, Irena Penha; Silva, Maria Rosa da; Freitas e Silva, Leila Milka (Revista Prevenção de Infecção e Saúde, 2023)
Introduction: Adolescence is a period of intense changes, doubts, and indecisions, making it an age group vulnerable to health-related risks, such as infection by the Human Immunodeficiency Virus (HIV). Aim: To describe the situation of vulnerability of adolescent students in relation to HIV infection and its association with individual and social factors. Outlining: Descriptive, cross-sectional, and quantitative study. Data collection took place online, with high school teenagers from a public school, using the student leaflet “Should I get tested for HIV/aids test?”. Data analysis was performed using the software JASP 0.9.1.0 and BioEstat 5.0. Results: Of the 126 participants, 81.7% had low to medium vulnerability to HIV infection and 18.3% had high vulnerability. Amongst the most vulnerable adolescents, the majority were aged between 18 and 19 years old, female, homosexual/bisexual, black, professed no religion or were non-Christian, with a stable sexual partner and were residents from the urban area. An association between the students’ level of vulnerability and place of residence was found (p=0.032; OR=2.71; 95% CI=1.07 - 6.89). Implications: Adolescents may be vulnerable to HIV, and actions aimed at sex education are important.